Damnatio memoriae. A Historical and Moral Revenge in Images - Irina-Andreea Stoleriu; Adrian Stoleriu (Anastasis: Research in Medieval Culture and Art, 2017)
The article suggestively called Damnatio memoriae. Historical and moral revenge in images is considering the analysis of a cultural, historical and artistic phenomenon practiced since ancient times in different cultures and civilizations, which literally consists in condemning the memory of certain remarkable personalities of the past, by deleting the names of the inscriptions, respectively by deteriorating, marking with distinctive signs (blackout, scribbling, etc.) or even completely destroying the images that represented them. As we will try to demonstrate, this kind of practice has a strong ethical connotation, offering, besides a series of genuine documents about historical events, a moralizing example based on a certain type of ideology specific to the space where they originated. Our work proposes to exemplify such a case, originating from the 16th century in Moldavia, referring to the personality and visual representations of Prince Iliaş who appears in various artistic representations, such as the votive paintings of Humor, Baia, Moldoviţa and Probota . It is worth noting from the beginning that the act of condemning memory was most often done as a sign of an epoch-end (dictatorship) and the beginning of a new one in which the recollection of the tyrant (or of that particular personality) was destroyed, and the images that reminded of him were vandalized. As history shows, when such a phenomenon took place, hatred of the dictators of the periods of sad remembrance was reflected, most of the time, upon the works of art that they represented, or the documents that mentioned them, without taking into any account the importance, value, costs or efforts made to achieve them.